Flavonol glycoside complanatoside A requires FOXO/DAF-16, NRF2/SKN-1, and HSF-1 to improve stress resistances and extend the life span of Caenorhabditis elegans - Tan, Lin; Zheng, Zhuo-Ya; Huang, Lv; Jin, Zhong; Li, Su-Lian; Wu, Gui-Sheng; Luo, Huai-Rong (Frontiers in Pharmacology, 2022)
Aging is associated with increased risk of most age-related diseases in humans. Complanatoside A (CA) is a flavonoid compound isolated from the herbal medicine Semen Astragali Complanat. CA was reported to have potential anti-inflammatory, analgesic, anti-anxiety, and hepatoprotective effects. In this study, we explored whether CA have anti-aging effect in Caenorhabditis elegans (C. elegans). Our results showed that CA exhibited improved physiological functions in aging worms, including enhanced locomotor capacity, reduced the accumulation of aging pigment. CA increased the lifespan of C. elegans by about 16.87%. CA could also reduce the accumulation of toxic proteins (α-synuclein and β-amyloid), delayed the onset of neurodegenerative disorders, such as Alzheimer's disease and Parkinson's disease in models of C. elegans. Further investigation revealed that CA require DAF-16/FOXO to extend the lifespan of C. elegans. CA could increase the antioxidation and detoxification activities regulated by transcription factor SKN-1 and heat resistance by activating HSF-1 mediated the expression of the chaperone heat shock proteins. our results suggest that CA could activate cellular protective pathways including DAF-16, SKN-1, and HSF-1, and is a potential anti-aging agent worth further research for development for pharmaceutical application.